Dermatophytosis among Schoolchildren in Three Eco-climatic Zones of Mali. - Oumar Coulibaly; Abdoulaye K Kone; Safiatou Niaré-Doumbo; Siaka Goïta; Jean Gaudart; Abdoulaye A Djimdé; Renaud Piarroux; Ogobara K Doumbo; Mahamadou A Thera; Stéphane Ranque (Public Library of Science (PLoS), 2016)
Dermatophytosis, and particularly the subtype tinea capitis, is common among African children; however, the risk factors associated with this condition are poorly understood. To describe the epidemiology of dermatophytosis in distinct eco-climatic zones, three cross-sectional surveys were conducted in public primary schools located in the Sahelian, Sudanian and Sudano-Guinean eco-climatic zones in Mali.Among 590 children (average age 9.7 years) the overall clinical prevalence of tinea capitis was 39.3%. Tinea capitis prevalence was 59.5% in the Sudano-Guinean zone, 41.6% in the Sudanian zone and 17% in the Sahelian eco-climatic zone. Microsporum audouinii was isolated primarily from large and/or microsporic lesions. Trichophyton soudanense was primarily isolated from trichophytic lesions. Based on the multivariate analysis, tinea capitis was independently associated with male gender (OR = 2.51, 95%CI [1.74-3.61], P<10(-4)) and residing in the Sudano-Guinean eco-climatic zone (OR = 7.45, 95%CI [4.63-11.99], P<10(-4)). Two anthropophilic dermatophytes species, Trichophyton soudanense and Microsporum audouinii, were the most frequent species associated with tinea capitis among primary schoolchildren in Mali.Tinea capitis risk increased with increasing climate humidity in this relatively homogenous schoolchild population in Mali, which suggests a significant role of climatic factors in the epidemiology of dermatophytosis.